Prevalence of hypertension among Malay adolescents in Putrajaya secondary schools, Malaysia, 2010 - Gyanchand Rampal, Lekhraj Rampal; Ng, Kai Choon; Izhar, Nur Izzati; Zulkafli, Farah Izzati; Ishak, Mohammad Nazrul; Ibrahim, Faisal; Syed Yahya, Sharifah Zainiyah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2011)
Background: In Malaysia, the prevalence of hypertension amongst adults aged 30 years and above has increased from 32.9% in 1996 to 40.5% in 2004 and to 42.6% in 2006. Information on the prevalence of hypertension among adolescents is lacking. Objective: to determine the prevalence of hypertension among Malay secondary school students in Putrajaya. Methods: A cross sectional study was carried out in Putrajaya, Malaysia. The sampling frame consisted of a list of all the 12 secondary schools in Putrajaya. Three schools were selected using table of random numbers. All Malay students aged 13 years old to 17 years old from the three selected school students were included in the study. Blood pressure was measured after the respondents had rested for at least 5 minutes using a standard mercury sphygmomanometer. Three blood pressure measurements were taken for each respondent. Systolic blood pressure [SBP] was defined as the average of three SBP readings and diastolic blood pressure [DBP] was defined as the average of three DBP readings. Data was analyzed using SPSS 18. Results: The overall mean SBP and DBP were 108.9 mmHg and 63.2 mmHg respectively. The prevalence of pre-hypertension and hypertension among the male was 16.2% and 12.9% respectively as compared to 5.8% and 10.2% respectively in the females. The overall prevalence of prehypertension and hypertension was 11.1% and 11.6% respectively. The prevalence increased with age (p<0.05). There was a significant positive correlation between BMI and SBP (r = 0.52, r2 = 0.27, p= 0.001) and BMI and DBP (r = 0.38, r2 = 0.15, p= 0.001). The mean SBP was significantly higher in males (111.7 mmHg) as compared to 106 mmHg in females (p<0.001). The mean DBP in males (63.5 mmHg) was slightly higher as compared to 62.9 mmHg in females but the difference was not significant. Conclusions: Prevalence of hypertension and pre- hypertension is high. There is an urgent need for implementation of a comprehensive CVD prevention program and routine blood pressure measurements should be taken in school children to improve the detection, prevention and treatment of hypertension.